2018
DOI: 10.4314/rejhs.v6i4.7
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic risk pattern among Nigerian hypertensive and diabetic patients undergoing follow-up visit in a tertiary hospital

Abstract: Objectives: Cardiovascular risk can be predicted using lipid ratios such as the atherogenic index which is defined as the base 10 logarithm of the ratio of plasma triglyceride (TG) to high density lipoprotein cholesterol (HDL-C)-it is a useful prognostic parameter for guiding timely interventions and has also been employed as a predictor of cardiovascular risk. However, this is rarely used in the clinical practice in developing countries including Nigeria. Methods: This study was a hospital-based cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
4
0
1
Order By: Relevance
“…Contrary to other studies 12 , 17 , 23 , we didn't show a significant relationship between AIP and LDL despite 78.4% of the study participants having elevated LDL probably the two measures assess different abnormalities in an individual. Whereas the importance of LDL cholesterol in the development of atherosclerosis is well documented, and it being the principal target for prevention of CHD, the heterogeneity of the LDL particles has been recently elucidated 24 Different forms of LDL that include small dense LDL particles and oxidized LDL have been described and these constitute the kinetic abnormalities of LDL other than the quantitative abnormality that is routinely assessed by the usual lipid profile.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to other studies 12 , 17 , 23 , we didn't show a significant relationship between AIP and LDL despite 78.4% of the study participants having elevated LDL probably the two measures assess different abnormalities in an individual. Whereas the importance of LDL cholesterol in the development of atherosclerosis is well documented, and it being the principal target for prevention of CHD, the heterogeneity of the LDL particles has been recently elucidated 24 Different forms of LDL that include small dense LDL particles and oxidized LDL have been described and these constitute the kinetic abnormalities of LDL other than the quantitative abnormality that is routinely assessed by the usual lipid profile.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are consistent with a study done in Nigeria by Bolarinwa et al that found a high AIP in 31.4% of diabetic and hypertensive patients attending a tertiary hospital 17 . This study is similar to ours in that they were both cross-sectional hospital-based studies with similar patients studied.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations